Capital and Interest Once More: I. Capital Vs. Capital Goods - Bohm-Bawerk, E. (Quarterly Journal of Economics, 1906)
Journal Article Capital and Interest Once More: I. Capital vs. Capital Goods Get access E. Böhm-Bawerk E. Böhm-Bawerk Vienna Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 21, Issue 1, November 1906, Pages 1–21, https://doi.org/10.2307/1883748 Published: 01 November 1906